The effect of topically extravirgin olive oil on the UVB-induced immunosuppression - AriefBudiyanto, Irianiwati, Vohanes Widodo Wirohadidjojo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Background: UVBradiation may act as an immunosuppressive agent through Langernans cells (LCs)depletion correlated with cyclobuthane pyrimidine dimer (CPD), as the most mutagenic photoproducts. Other studies showed that olive oil can prevent various human cancers, which are defect of immune-surveillance. The effect of olive oil in the UVBinduced LCs depletion is still unclear. Objective: To discover the topical effect of extravirgin-olive-oil in the LCs depletion. Methods: A simple experimental study was performed on foreskins collected from 8 circumcised boys. Each of them was cut into 3 pieces of 0.5 cm2, grouped randomly to: (Olive oil+ UVB)group, (placebo + UVB)group, and unirradiated group. They were cultured in DMEM for 24 hours, irradiated with 100mJs/cm2 UVB, and olive oil or placebo were then applied immediately after irradiation. All specimens were fixed in buffered-formalin, paraffin blocked, and cut to be 2 slides, and each of them was stained with anti-CD 1a or anti-CPD antibody. The pixels of AEC signats were digitally counted based on Photoshops selected color histogram.The pixel means of various groups were analyzed by Kruskal-Wallis test and post hoc analysis by Mann Whitney test. Results: Olive oil treated groups showed a very significant (P